LEGAL MODELS OF A SYSTEM OF PROPERTY LAW IN CIVIL LEGISLATION - Харченко, Георгій (Київський національний університет імені Тараса Шевченка, 2024)
Background. The article reveals and compares the main characteristics of two models of building a system of property law in civil legislation that compete with each other in the world legal doctrine. One of them, which historically arose at the end of the 19th century in Germany, reveals property law as a system of legal relations, which, according to the intention of its developers, should correspond to the main direction of civil law regulation with a focus on relations, not rights. However, the internal contradictions inherent in such a concept made it necessary to substantiate its expediency in law due to the dualism of the legal nature of civil rights, including property rights, when the latter were considered not only as a legal connection between a person and an object (subject-object approach), and primarily as a relationship between persons in relation to the object (subject-subject approach). As a result, in property law we can see such types of property rights that are not typical and are not actually varieties of property rights. The property nature of these rights is proven not through the characterization of the content of these rights (qualifying features), but through the characterization of the legal relationship in which such rights can arise, exercise and terminate. Methods. To achieve the purpose of the study, the author used the following methods: formal and logical, dialectical, and comparative. Results. The author notes that the working group on recodification of the civil legislation was officially established by the Cabinet of Ministers of Ukraine and included all the shortcomings inherent in the model of the system of property law as legal relationships in the Concept for Updating the Civil Code of Ukraine (2020). In view of this, among other things, it is proposed to introduce into the civil legislation of Ukraine such new types of property rights, which actually have a binding, not a property, nature. Conclusions. It is proved that the model of the system of property law as relationships does not correspond to the legal system of Ukraine, since the civil law doctrine clearly distinguishes and does not equate the concepts of "legal relations" and "civil rights" in law, and because the nature of property rights is different from the nature of property relations and is even broader. The civil legislation in Ukraine should apply the concept of property law as a system of property rights, where the latter are determined exclusively by the characteristics of the connection between a person and an object (qualifying features of property rights).

Вступ. Здійснено порівняльний аналіз основних характеристик двох конкуруючих між собою у світовій доктрині права моделей побудови системи речового права в цивільному законодавстві. Одна з них, що історично виникла наприкінці ХІХ століття в Німеччині, розкриває речове право як систему правовідносин, що за задумом її розробників мало б відповідати основному напряму цивільно-правового регулювання з фокусом на відносини, а не суб'єктивні права. Проте внутрішні суперечності, закладені у такій концепції, змусили обґрунтовувати її доцільність у праві через дуалізм правової природи цивільних прав, речових у тому числі, коли останні розглядались не лише як юридичне відношення особи до об'єкта (суб'єктно-об'єктний підхід), а насамперед як відносини між особами щодо об'єкта (суб'єктно-суб'єктний підхід). Як наслідок у речовому праві з'явились такі не притаманні йому й, насправді, неречові різновиди речових прав, речова природа яких доводиться не через характеристику змісту цих прав (кваліфікаційні ознаки), а через характеристику правовідносин, у яких такі права можуть виникати, здійснюватися і припинятися. Методи. Для досягнення мети дослідження використано такі методи, як формально-логічний, діалектичний, порівняльний. Результати. Показано, що в Концепції оновлення Цивільного кодексу України (2020), яка була видана офіційно утвореною Кабінетом Міністрів України робочою групою з рекодифікації цивільного законодавства, так само мають місце всі ті недоліки, що притаманні моделі системи речового права як правовідносин, а тому, окрім іншого, запропоновано введення у цивільне законодавство України таких нових різновидів речових прав, які насправді мають зобов'язальну, а не речову природу. Висновки. Доведено, що модель системи речового права як правовідносин не відповідає правовій системі України, позаяк цивілістична доктрина чітко розмежовує і не ототожнює у праві поняття "правовідносини" і "цивільні права", а оскільки природа речових прав відмінна від природи речових правовідносин, то в Україні в цивільному законодавстві має бути застосована концепція речового права як системи речових прав, де останні визначаються виключно через характеристику зв'язку особи з об'єктом (кваліфікаційні ознаки речових прав).
ПРАВОВІ МОДЕЛІ СИСТЕМИ РЕЧОВОГО ПРАВА В ЦИВІЛЬНОМУ ЗАКОНОДАВСТВІ
Keywords: property rights; system of property law; property relations; recodification of civil legislation; речові права; система речового права; речові правовідносини; рекодифікація цивільного законодавства